Переописание свободноживущей нематоды Axonolaimus seticaudatus Platonova, 1971 из залива Посьета Японского моря - Белогуров, О.И. (Вестник зоологии, 1979)
A detailed redescription is given to Axonolaimus seticaudatus Platonova, 1971 from the Possjet Bay of the Sea of Japan. The species is found also in the Amur Bay of the Gulf of Peter the Great. The frontal pyramid of the stoma consists of 6 two-apex lobes which are able of protruding and turning out. Amphids are covered with fine drawings. Ovaries are direct, sometimes with loops on apexes; spermathecas are solitary, communicated with special urine chambers by canals. The testicle is only one and begins at the level of the oesophagus end.